Plano Educacional Individualizado (PEI) para estudantes com deficiência: um protocolo para utilização nas instituições de ensino - Santos, Jéssica Rodrigues (2023)
With the increase in Brazilian public policies on Special Education from the Perspective of Inclusive Education, enrollment of public students in Special Education has been growing at different levels and stages of education. The same occurs with these students' access to the final years of Elementary and Secondary Education in regular education institutions. In this scenario, questions arise about guaranteeing participation, learning and success. One of the supports suggested by the literature to ensure the necessary conditions for the schooling of Special Education students, especially those with disabilities, has been individualized planning. This process requires collaborative strategies involving different members of educational institutions based on a comprehensive assessment of the student with disabilities in a collective decision-making process that will result in a written document. As it is a device yet to be provided for in Brazilian legislation, as is the case in many countries, educational spaces have many doubts about how to prepare the Individualized Educational Plan (IEP). Thus, the central question in this study is what an Individualized Educational Plan (IEP) protocol would look like that would contribute to favoring educational policies for the permanence, progression and transition to adult life of people with disabilities. The study's general objective was to develop and validate a protocol for preparing the Individualized Educational Plan (IEP) for students with disabilities in Basic Education. The specific objectives were: a) Compile and systematize an IEP protocol based on proposals found in practice and specialized literature in the area; b) Validate the content and semantics of the IEP protocol items with two groups of different judges: professionals and academics from the area community; c) Produce an improved and validated version of the IEP protocol. The research uses a qualitative approach based on the Design Science Research (DSR) method, adopted in education to create prototypes or educational products. In the first validation stage, 106 participants (professionals and members of Brazilian Federal Institutes) contributed to this research. In the second stage, 14 researchers in the field of special education contributed. Data was obtained through questionnaires on Google Forms. Participants were invited to rate the relevance and vocabulary of each item in the protocol. The items were analyzed quantitatively and qualitatively. The results were procedural and specific at each stage, resulting in a protocol built based on literature and evaluated by different judges called ProPEI. The ProPEI is a broad document to be completed by different hands after reflection and sharing ideas. The document was structured with the following fields: 1. Information from the educational institution; 2. Authorization term for preparing the IEP; 3. Student profile (individual characteristics, skills and challenges); 4. Characterization of the family and their expectations regarding the student’s development; 5. Information about the previous schooling process; 6. Description of the student's initial repertoire; 7. Characterization of team members; 8. Distinction of areas of knowledge that require adaptation or differentiation processes in teaching; 9. Establishment of specific learning objectives (short, medium and long-term goals); 10. Development of teaching strategies and teaching materials; 11. Necessary adjustments in the student's teaching and learning evaluation process; 12. Definitions of dates to monitor the student's trajectory and the adequacy of the IEP. The participants who evaluated the protocol consider it a document with great potential to contribute to the school's inclusion of students who need it. It is expected that this study and the protocol developed in it will contribute to the elaboration of the IEP as support to guarantee the promotion of practices that favor the participation and learning of students with disabilities in schools.